Application of a Natural Antioxidant from Grape Pomace Extract in the Development of Bioactive Jute Fibers for Food Packaging - Cristina Cejudo-Bastante; Paloma Arjona-Mudarra; María Teresa Fernández-Ponce; Lourdes Casas; Casimiro Mantell; Enrique J. Martínez de la Ossa; Clara Pereyra (MDPI AG, 2021)
There is an increasing demand for the use of new food packaging materials. In this study, natural jute fibers impregnated with a Petit Verdot Red Grape Pomace Extract (RGPE) was proposed as a new active food packaging material. Pressurized Liquid Extraction (PLE) and Enhanced Solvent Extraction (ESE) techniques were employed to obtain the bioactive RGPE. Afterward the supercritical solvent impregnation conditions to obtain RGPE-natural jute fibers were studied, by varying pressure, modifier percentage and dried RGPE mass. PLE technique offered the highest bioactive extract at 20 MPa, 55 °C, 1 h residence time using C2H5OH:H2O (1:1 v/v), providing an EC50 of 3.35 ± 0.25 and antibacterial capacity against Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa (MIC of 12.0, 1.5 and 4.0 mg/mL RGPE respectively). The natural jute fibers impregnated with 3 mL of that RGPE (90 mg/mL) at 50 MPa and 55 °C generated the most efficient packing material with regards to its food preservation potential.